Sustainable materials: a linking bridge between material perception, affordance, and aesthetics - Strappini, Francesca; Fagioli, Sabrina; Mastandrea, Stefano; Scorolli, Claudia (Frontiers in Psychology, 2024)
The perception of material properties, which refers to the way in which individuals perceive and interpret materials through their sensory experiences, plays a crucial role in our interaction with the environment. Affordance, on the other hand, refers to the potential actions and uses that materials offer to users. In turn, the perception of the affordances is modulated by the aesthetic appreciation that individuals experience when interacting with the environment.By designing materials with clear and intuitive affordances, and aesthetic qualities, users can intuitively perceive how to interact with them, reducing the learning curve and promoting sustainable usage. This process can lead to increased user engagement, extended product lifecycles, and reduced waste generation.Although material perception, affordances, and aesthetic appreciation are recognized as essential to fostering sustainability in society, only a few studies have investigated this subject matter systematically and their reciprocal influences. This scarcity is partially due to the challenges offered by the complexity of combining interdisciplinary topics that explore interactions between various disciplines, such as psychophysics, neurophysiology, affective science, aesthetics, and social and environmental sciences.Outlining the main findings across disciplines, this review highlights the pivotal role of material perception in shaping sustainable behaviors. It establishes connections between material perception, affordance, aesthetics, and sustainability, emphasizing the need for interdisciplinary research and integrated approaches in environmental psychology. This integration is essential as it can provide insight into how to foster sustainable and durable changes.